Nuances relacionadas ao princípio da isonomia e equiparação salarial - Moura, Rodolfo Italo Weber Del (2018)
The purpose of this monograph is to analyze wage issues related to wage equalization and wage equalization, analyzing its evolution and application in Brazilian Labor Law, observing the material aspects of Article 461 of the CLT of May 1, 1943 and its requirements under constitutional principle, aiming to clarify the main doubts encountered by the operators and applicators of the law in the practical application of the Constitutional Principle of the Salary Isonomy. It deals mainly with the new wording of article 461 of the CLT brought by law 13467 of July 13, 2017, taking into account the current judgements. The subjects are studied trying to show historical evolutions in a clear and objective way. The research was developed through analysis of legislation, doctrine and jurisprudence, verifying the evolution of the institutes, confronting traditional precepts to the current concepts. Concluding on the importance of the issue in the legal and socioeconomic context of the country, highlighting in particular its fundamental relevance in the lives of workers, who can not accept wage discrimination, the implementation of employer abuses, encouraged by fear of economic problems and rising current unemployment in Brazil